FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA ANAK SEKOLAH SD NEGERI 8 BATU - niar, hasniar (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Nutritional problems in primary school-aged children are influenced by various factors, including diet, economic level, parental education and school environment. Children who do not receive balanced nutrition are more prone to stunting, wasting and obesity, which can impact the quality of human resources in the future. The 2022 SSGI results show a decrease in national stunting from 24.4% (2021) to 21.6% (2022). Meanwhile, wasting increased from 7.1% to 7.7%. This study uses a quantitative approach with a cross-sectional study method that analyzes data at one specific time. The research location was SDN 8 Batu, Leppangeng Village, Pitu Riase District, Sidendreng Rappang Regency. The population of this study were all 53 students of SDN 8 Batu and the entire population was sampled using the total sampling method. The results showed a relationship between diet and nutritional status, while physical activity, economy and school environment did not have a significant relationship with nutritional status.